2020
DOI: 10.1111/cdev.13454
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of the Link Between the Approximate Number System and Symbolic Math Ability

Abstract: Experimentally manipulating Approximate Number System (ANS) precision has been found to influence children's subsequent symbolic math performance. Here in three experiments (N = 160; 81 girls; 3-5 year old) we replicated this effect and examined its duration and developmental trajectory. We found that modulation of 5year-olds' ANS precision continued to affect their symbolic math performance after a 30-min delay. Furthermore, our cross-sectional investigation revealed that children 4.5 years and older experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 59 publications
(120 reference statements)
0
17
0
1
Order By: Relevance
“…In support of this perspective, behavioral data have shown that performance on ANS tasks and symbolic number comparison tasks are both characterized by ratio effects (e.g., Holloway & Ansari, 2009); longitudinal and meta-analytic studies have consistently shown a significant relation between the ANS and mathematics achievement (Chen & Li, 2014;Fazio et al, 2014;Schneider et al, 2017); some experimental training studies have shown evidence that improving children's ANS can lead to improvements in their mathematics achievement (Hyde et al, 2014;Wang et al, 2020); and data from neuroimaging studies have implicated the same region of the brain, the Intraparietal Sulcus (IPS), in the processing of approximate and exact, symbolic numbers (Eger et al, 2009;Nieder & Dehaene, 2009). However, this perspective has been challenged by other researchers, who suggest that children's understanding of exact symbolic numbers emerges separately from their ANS (Leibovich & Ansari, 2016;Lyons & Ansari, 2015;Reynvoet & Sasanguie, 2016).…”
Section: Numerical Development In Preschool: Examining Potential Mediators Of Children's Ans and Mathematics Achievementmentioning
confidence: 96%
See 1 more Smart Citation
“…In support of this perspective, behavioral data have shown that performance on ANS tasks and symbolic number comparison tasks are both characterized by ratio effects (e.g., Holloway & Ansari, 2009); longitudinal and meta-analytic studies have consistently shown a significant relation between the ANS and mathematics achievement (Chen & Li, 2014;Fazio et al, 2014;Schneider et al, 2017); some experimental training studies have shown evidence that improving children's ANS can lead to improvements in their mathematics achievement (Hyde et al, 2014;Wang et al, 2020); and data from neuroimaging studies have implicated the same region of the brain, the Intraparietal Sulcus (IPS), in the processing of approximate and exact, symbolic numbers (Eger et al, 2009;Nieder & Dehaene, 2009). However, this perspective has been challenged by other researchers, who suggest that children's understanding of exact symbolic numbers emerges separately from their ANS (Leibovich & Ansari, 2016;Lyons & Ansari, 2015;Reynvoet & Sasanguie, 2016).…”
Section: Numerical Development In Preschool: Examining Potential Mediators Of Children's Ans and Mathematics Achievementmentioning
confidence: 96%
“…Indeed, recent experimental studies have shown that reading interventions focusing on spatial and numerical words (e.g., more, less, near, far) can lead to improvements in both children's mathematical language and mathematics achievement (Purpura et al, 2021;Hassinger-Das et al, 2015;Purpura et al, 2016). This contrasts with the mixed findings of studies to promote children's mathematics achievement by improving their ANS (Honoré & Noël, 2016;Park et al, 2016;Wang et al, 2020). Future research should investigate whether interventions focused on improving the ANS benefit from being combined with interventions that support mathematical language.…”
Section: Mathematical Language As a Full Mediatormentioning
confidence: 99%
“…All variants of the game involved tracking and comparing collections of objects on the basis of number and were equated for general gameplay, expectations about the training, and other cognitive and behavioral task demands. We chose nonsymbolic numerical comparison as the basis of all training variants because a) it is numerical in nature b) it engages core systems available to all participants and c) non-symbolic numerical magnitudes and symbolic numbers become linked over development [e.g., [70][71][72]. Five different training variants presented different types of numerical content (see Fig 1A-E).…”
Section: Current Approachmentioning
confidence: 99%
“…日后的代数以及一般性数学表现 (Bailey et al, 2012;Mou et al, 2016;Siegler et al, 2011;Siegler & Pyke, 2013) 通信作者: 牟毅, E-mail: mouyi5@mail.sysu.edu.cn 分分数的数值大小、将它们按数值排序或转换分 数和小数 (Bailey et al, 2014; Ni & Zhou, 2005; Feigenson et al, 2004), Gilmore, 2009;Sasanguie et al, 2012;Schneider et al, 2017 (vanMarle et al, 2014;Chu et al, 2016;Mou et al, 2018;Starr et al, 2018;Wang et al, 2020 (Hyde & Mou, 2015;Mock, et al, 2018;Nieder, 2016;Piazza, 2010)…”
Section: )。实证研究发现儿童的分数知识确能预测其unclassified